PENYULUHAN KESEHATAN GIGI DAN MULUT KEPADA ANAK DI DESA BUG-BUG KECAMATAN LINGSAR - Fitriana, Dhea Rizkiya; Noval, Khamada; Fajri, Muhammad; Diandra4, Amalia; Nazari, Sulhan; Biomantara, I Nyoman Hari; Salsabina, Elsa Thalia; Cahya, Baiq Karunia Dwi; Islamiah, Nur; Nurkhaliza, Ema; Sideman, Ida Ayu Oka Suwati (Jurnal Wicara, 2023)
Dental and oral health is very important for us to maintain, because teeth are one of the organs that play an important role in the nutrition that enters our body. When teeth and gums are not cared properly, they can cause damage and this can lead to pain, masticatory disorders, canker sores, plaque, and so on. Maintaining healthy teeth should be done early on, so as to create healthy lifestyle habits. Counseling has the goal of changing individual behavior for the better and it is hoped that children's knowledge about dental and oral health will increase and can increase awareness and change lifestyle habits. Implementation counseling to share knowledge related to how to care for dental and oral health. Counseling is done by giving material and demonstrating how to brush your teeth properly and correctly. How to draw interesting material can make the attention of the participants focused on the speaker so that during a demonstration on how to brush their teeth, the enthusiasm of the participants soared and made the counseling event livelier. From the dental and oral health education program that has been implemented, satisfactory results have been obtained. All participants who attended dental and oral health counseling received knowledge about the importance of maintaining healthy teeth and how to maintain a healthy lifestyle. From this activity, it is expected that participants can act as mediators of information about oral health for their environment.